Intercultural Investigation of Prospective Preschool Teachers' Perceptions on the Metaphors Related to Preschool Child and Teacher - Küçükturan, Ayşe Güler; Kocaman, Orhan (Bartın Üniversitesi, 2017)
This research was carried out to examine Turkish and Spanish prospective preschool teachers' perceptions on the metaphors related to the concept of preschool child and teacher and to determine the cultural differences within this framework.Metaphors stated by Spanish prospective preschool teachers on preschool child were gathered under six categories as learning child, formed child, child as a source of learning, child with potential, growing and developing child, child as a source of joy, however, their metaphorical perceptions on preschool teacher centred around following five categories; informant teacher, teacher learning together, caring and protecting teacher, guiding teacher and core teacher. Metaphors stated by Turkish prospective preschool teachers on preschool child comprised six categories as learning child, formed child, exploring and explored child, raised child, child to be protected, child as a source of joy, whereas their metaphorical perceptions on preschool teacher were composed of six categories as informant teacher, teacher learning together, caring and protecting teacher, forming teacher, gifted teacher and considerate teacher.

Bu araştırma, Türk ve İspanyol okul öncesi öğretmen adaylarının çocuk ve okulöncesi öğretmeni kavramına ilişkin sahip oldukları metaforları incelemek ve kültürel farklılıkları belirlemek amacıyla yapılmıştır. İspanyol öğretmen adaylarının çocuk  metaforlarından öğrenen çocuk, şekillendirilen çocuk, birlikte öğrenilen çocuk, potansiyeli olan çocuk, büyüyen gelişen çocuk ve neşe veren çocuk olmak üzere 6, öğretmen metaforlarından ise bilgi veren öğreten öğretmen, birlikte öğrenen öğretmen, bakım veren koruyan kollayan öğretmen, rehber olan öğretmen, temel olan yüklenen öğretmen olmak üzere 5 kategori oluşmuştur. Türk öğretmen adaylarının çocuk metaforlarından öğrenen çocuk, şekillendirilen çocuk, keşfedilen keşfeden çocuk, yetiştirilen çocuk, korunması gereken çocuk, neşe veren çocuk olmak üzere 6, öğretmen metaforlarından ise bilgi veren öğreten öğretmen, birlikte öğrenen öğretmen, bakım veren koruyan kollayan öğretmen, şekil veren öğretmen, üstün özellikleri olan öğretmen, sevecen öğretmen olmak üzere 6 farklı kavramsal kategori oluşmuştur.
Okul Öncesi Öğretmen Adaylarının Çocuk ve Öğretmen ile İlgili Metaforlarının Kültürlerarasi İncelenmesi